(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Home automation is the process of controlling electronic devices automatically through other electronic devices which includes cell phones, controllers etc. Home automation can be classified into three types on the basis of networks: power line based, wired and wireless home automation system. This paper speaks about the home automation system, a comparison of the features and architectures which have been used in the various technologies of home automation system. The purpose of this paper is to help the people to understand about the home automation system and to get an overall view about the technology. The intention of this paper is to help the reader to understand the home automation system. Keywords: Zigbee, WiFi, Smart Home, GSM, Routing